Review Criminology To Action Criminal Human Trafficking (TPPO) - Rheza Fahruddin, Andi Muhammad; Badaru, Baharuddin; Salle, Salle (Faculty of Law, Universitas Muslim Indonesia, 2025)
Study This to study review criminology to act criminal human trafficking (TPPO), as well as factors that become reason the occurrence abuse narcotics in women in Makassar City. The method used is study law empirical with approach regulation legislation and approaches case For analyze existing regulations​ as well as challenge in enforcement law . Research results show that TPPO can understood as complex crimes , involving​ various factor economic , social and network criminal organized . Enforcement law to practice This faced with factors like lack of coordination between institutions and the lack of understanding public about risk law . Research This recommend improvement education law for public as well as strengthening capacity apparatus enforcer law For handle TPPO cases in general more effective . Research conclusion This emphasize importance protection comprehensive law​ For prevent and eradicate TPPO in Indonesia.